Dynamics of coordination-clusters in long-term rehabilitation. Issue 3 (5th December 2016) - Noori, Nadia Saad; Weber, Christina
Abstract : Purpose: The purpose of this paper is to introduce a novel approach to studying disaster management operations: the emergence of coordination-clusters in long-term rehabilitation projects and innovation dynamics in coordination-clusters. Design/methodology/approach: The problem addressed is examining the coordination dynamics in long-term rehabilitation operations. A mixed methods research approach was adopted where a combination of qualitative and quantitative techniques was used for data collection and analysis to study the phenomenon of the coordination evolution in long-term rehabilitation projects. Findings: The results indicate resilience in the behavior of involved actors from different organizations as they re-organize into coordination-clusters and collectively work to overcome the unfolding challenges of long-term rehabilitation projects in areas affected by major disaster. Research limitations/implications: The results provide some answers to the question of how to map and analyze the phenomenon of coordination-clusters and their consequent coordination dynamics, and thereby steps to redesign the approach to execute long-term rehabilitation projects in places affected by major disasters. Practical implications: The combination of Actor-network theory and critical incident technique with social network analysis and community detection provides an integrated network-based view of coordination dynamics in long-term recovery operations. Such perspective would broaden the empirical basis for the planning and management of complex disaster management operations. Originality/value: The results of the research offer a new approach to study coordination dynamics in disaster management operations. The proposed method provides a tool to examine the evolution of processes involved with the recovery phase of a disaster management cycle.